2006
DOI: 10.1038/modpathol.3800629
|View full text |Cite
|
Sign up to set email alerts
|

TTF-1 and p63 for distinguishing pulmonary small-cell carcinoma from poorly differentiated squamous cell carcinoma in previously pap-stained cytologic material

Abstract: In histology and cell block sections, antibodies to thyroid transcription factor-1 (TTF-1) and p63 have been demonstrated to be useful markers for distinguishing between small-cell lung carcinoma and poorly differentiated pulmonary squamous cell carcinoma. In this study, we assessed the utility of TTF-1 and p63, as an antibody panel, for differentiating between these two neoplasms in previously Papanicolaou (Pap)-stained cytologic smears and cytospin slides. Twenty-six lung carcinomas (13 small-cell lung carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 22 publications
4
70
0
6
Order By: Relevance
“…In the absence of these, accuracy of cell typing for NSCLC is only 44%, but when cell blocks are prepared and immunohistochemical staining is performed, this increases to .80%, which is comparable with that reported previously for bronchial biopsies [18]. Other groups have described methodologies for immunohistochemical staining of previously stained Papanicolaou slides [21] and while this might allow some further information to be obtained in those cases where no cell block is available, the ability to use a panel of antibodies to optimise diagnosis is not possible with this approach. The importance of having cell blocks containing tumour cells for immunohistochemistry has, in our personal experience, also been useful in identifying or confirming the presence of metastatic carcinoma from sites other than lung.…”
Section: Discussionsupporting
confidence: 66%
“…In the absence of these, accuracy of cell typing for NSCLC is only 44%, but when cell blocks are prepared and immunohistochemical staining is performed, this increases to .80%, which is comparable with that reported previously for bronchial biopsies [18]. Other groups have described methodologies for immunohistochemical staining of previously stained Papanicolaou slides [21] and while this might allow some further information to be obtained in those cases where no cell block is available, the ability to use a panel of antibodies to optimise diagnosis is not possible with this approach. The importance of having cell blocks containing tumour cells for immunohistochemistry has, in our personal experience, also been useful in identifying or confirming the presence of metastatic carcinoma from sites other than lung.…”
Section: Discussionsupporting
confidence: 66%
“…Immunohistochemistry markers, such as cyto-keratin 7/8 (CK7/8), P63, and thyroid transcription factor-1 (TTF-1) were chosen to discriminate components of non-small cell lung cancer. Neuron specific enolase (NSE), and chromogranin (ChrA) were commonly used to recognize SCLC components (Kalhor et al, 2006;Bishop et al, 2010). This study was approved by the Institutional review board of Shanghai pulmonary hospital and the Informed Consent Forms (ICF) was signed by each eligible patient before the initiation of any trial related procedure.…”
Section: Patientsmentioning
confidence: 99%
“…Immunohistochemistry with antibodies such as p63, TTF-1 and keratins 5/6/7/14/17, CD15 and thrombomodulin is currently used to distinguish pulmonary squamous cell carcinomas from adenocarcinomas. [4][5][6] Epithelial cells are characterized by tight junctions, which seal their apical regions in a gasket-like manner, thus preventing the free diffusion of solutes (including growth factors and pathogens) across extracellular luminal and basal compartments. Recent studies have shown that some tight junction proteins are involved in the regulation of epithelial proliferation and differentiation (reviewed by Matter et al 7 ).…”
mentioning
confidence: 99%